Вплив науково-технічного прогресу на розвиток ринку праці - Сидоренко, Павло Олександрович (My University, 2015)
У статті проаналізовано вплив надбань науково-технічного прогресу на формування сучасних тенденцій розвитку ринку праці. Розглядається вплив нових технологій на трансформацію відповідного соціально-економічного середовища, процесів виробництва, самих продуктів та ролі людської праці як фактору виробництва. Запропоновано науково-практичні рекомендації щодо максимізації позитивного ефекту від згаданих змін для функціонування ринку праці та мінімізації відповідних ризиків. The author analyzes the influence of technological change on the current labour market trends. Namely, the effects of new technology on the social and economic environment, processes of production, products and labour as a factor of production. New information and communication technologies considerably influence contemporary business models - i.e. fuel weightless companies and sharing economy - as well as general social and economic environment – i.e. automation, equipment and tools improvement promote productivity growth, etc. Extremely dynamic, challenging, and stressful work environment can reduce internal motivation and aggravate the problem of voluntary unemployment. Technological change promotes a constant professional development and lifelong learning, but a low-skilled labour is still a matter of concern, as well as the gap between productivity and compensation growth. Although numerous online courses, distant employment, and development of e-entrepreneurship can contribute to resolution of these issues, a customized policy is required. This policy should take into account the role of the private sector in R&D, encouraging innovation and growth. But further technological development should not be limited to the gadgetization, although it`s impossible to eliminate commercial drivers of innovation in a mid-term period. Based on the results of this research, the author suggests a list of practical recommendations aimed at the maximization of positive effects of the above-mentioned changes on the labour markets and mitigation of relevant risks. Interesting fields of further research are a phenomenon of labour intensity decrease in the information economy, gap between compensations and skills, etc.
Keywords: ринок праці; продуктивність праці; безробіття; електронне підприємництво; labour market; labour productivity; unemployment; eenterpreneurship; кафедра міжнародної економіки